1991
DOI: 10.1093/genetics/128.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of mutants defective in early steps of meiotic recombination in the yeast Saccharomyces cerevisiae.

Abstract: Using a selection based upon the ability of early Rec- mutations (e.g., rad50) to rescue the meiotic lethality of a rad52 spo13 strain, we have isolated 177 mutants. Analysis of 56 of these has generated alleles of the known Rec genes SPO11, ME14 and MER1, as well as defining five new genes: REC102, REC104, REC107, REC113 and REC114. Mutations in all of the new genes appear to specifically affect meiosis; they do not have any detectable mitotic phenotype. Mutations in REC102, REC104 and REC107 reduce meiotic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…A number of yeast genes have been described, mutations of which decrease meiotic recombination, sporulation and spore viability, the two latter defects being suppressed by a s p o l 3 mutation: RAD50 (MA-LONE and ESPOSITO 198 1 ; ALANI, PADMORE and KLECKNER 1990); SPOl I (KLAPHOLZ, WADDELL and ESPOSITO 1985), REDl ROEDER 1988, 1990), HOPI (HOLLINSWORTH and BYERS 1989), ME14 (MENEES and ROEDER 1989), MER1 (ENGE-BRECHT and ROEDER 1989), MER21REC107 (ENGE-BRECHT, HIRSCH and ROEDER 1990;COOL and MA-LONE 1990), RECl02 (MALONE et al 1991;BHAR-CAVA, ENCEBRECHT and ROEDER 1992), MEKIIMRE4 (ROCKMILL and ROEDER 199 1 ;LEEM and OGAWA 1992). The ability of mutations leading to reduced sporulation and spore viability to be rescued by a s p o l 3 mutation is generally interpreted to mean that the corresponding genes function at "early" stages in the meiotic recombination process (MALONE et al 1991;PETES, MALONE and SYMINGTON 1991). Properties of s p o l 3 xrs2 double mutants suggest that XRS2 represents a novel member of the group of "early" meiotic Rec genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of yeast genes have been described, mutations of which decrease meiotic recombination, sporulation and spore viability, the two latter defects being suppressed by a s p o l 3 mutation: RAD50 (MA-LONE and ESPOSITO 198 1 ; ALANI, PADMORE and KLECKNER 1990); SPOl I (KLAPHOLZ, WADDELL and ESPOSITO 1985), REDl ROEDER 1988, 1990), HOPI (HOLLINSWORTH and BYERS 1989), ME14 (MENEES and ROEDER 1989), MER1 (ENGE-BRECHT and ROEDER 1989), MER21REC107 (ENGE-BRECHT, HIRSCH and ROEDER 1990;COOL and MA-LONE 1990), RECl02 (MALONE et al 1991;BHAR-CAVA, ENCEBRECHT and ROEDER 1992), MEKIIMRE4 (ROCKMILL and ROEDER 199 1 ;LEEM and OGAWA 1992). The ability of mutations leading to reduced sporulation and spore viability to be rescued by a s p o l 3 mutation is generally interpreted to mean that the corresponding genes function at "early" stages in the meiotic recombination process (MALONE et al 1991;PETES, MALONE and SYMINGTON 1991). Properties of s p o l 3 xrs2 double mutants suggest that XRS2 represents a novel member of the group of "early" meiotic Rec genes.…”
Section: Discussionmentioning
confidence: 99%
“…Meiotic defects of rad52 diploids are not suppressed in the presence of a s p o l 3 mutation (MALONE and ESPOSITO 198 1 ;MALONE 1983) suggesting that RAD52 acts at later stages of the meiotic recombination process. However, addition to s p o l 3 rad52 diploids of a mutation in some of the "early" Rec genes improves sporulation and spore viability (MALONE 1983;ENCEBRECHT and ROEDER 1989;ME-NEES and ROEDER 1989;MALONE et al 1991;BHAR-CAVA, ENCEBRECHT and ROEDER 1992). If xrs2 mutation confers a block in recombination prior to the RAD52 step, sporulation and spore viability should be rescued in s t 0 1 3 xrs2 rad52 diploids.…”
Section: Discussionmentioning
confidence: 99%
“…Discovery of Top6BL in plants and mouse led to identification of putative B subunits in yeasts and flies. This protein in S. cerevisiae , Rec102, was long known to be important for Spo11 activity 16 , 17 , but its relationship with the B subunit had remained unnoticed. Structural modeling suggested that the yeast and fly B-type subunits lack the GHKL domain that mediates ATP-dependent dimerization in Topo VI, whereas the mouse and plant counterparts contain a degenerate version of this domain 10 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Deletion mutations in RAD5O prevent the formation of meiosis-specific DSBs (3, 7), whereas mutations in RADS1 and RAD52 lead to the accumulation of abnormally degraded forms of DSBs (58). The whole body of evidence suggests that RAD5O belongs to a group of genes that function early in the meiotic recombination pathway, whereas RAD51 and RAD52 act later during the process, after the initiation steps of meiotic recombination have been completed (36).…”
mentioning
confidence: 99%